Direct WIMP detection rates for transitions in isomeric nuclei - Smirnov, Mikhail; Yang, G.; Novikov, Yu N.; Vergados, J. D.; Bonatsos, D. (Nuclear Physics B, 2024)
The direct detection of dark matter constituents, in particular the weakly interacting massive particles (WIMPs), is central to particle physics and cosmology. In this paper we study WIMP induced transitions from isomeric nuclear states for two possible isomeric candidates: Ta180 and Ho166. The experimental setup, which can measure the possible decay of Ta180 induced by WIMPs, was proposed. The corresponding estimates of the half-life of Ta180 are given in the sense that the WIMP-nucleon interaction can be interpreted as ordinary radioactive decay.
CRIS-Team Scopus Importer:2024-06-28

Light dark bosons in the JUNO-TAO neutrino detector - Smirnov, Mikhail; Yang, Guang; Liao, Jiajun; Hu, Zhuojun; Ling, Jiajie (Physical Review D, 2021)
This work presents a sensitivity study of a reactor liquid scintillator detector to three kinds of dark bosons with masses below 1 MeV, such as dark photons, axion-like particles, and light scalar bosons. The JUNO-TAO detector with Taishan nuclear reactor is taken as a reference. With a proposed 180 days of data taking, the best sensitivity result at the level of similar to 10(-5) 95% C.L. is achieved for dark photons with an optimized signal to background ratio for the electron coupling constant gX through inverse Compton-like scattering. Similar calculations are completed for axion-like particles and scalar bosons. The background systematic uncertainty presents as the main limiting factor for the further sensitivity improvement. Several remarks are made to the controversial analysis for the NEOS experiment. Additionally the differential and the inverse differential cross sections have been derived for all three boson types and their interactions with electrons in liquid scintillator.
CRIS-Team WoS Importer:2022-02-04

Open-Science Integration of a Combined Analysis of KM3NeT and CTA into the EOSC Infrastructure - Smirnov, Mikhail (Proceedings of Science, 2024)
KM3NeT is deep-sea neutrino research infrastructure in the Mediterranean Sea, including a cubic kilometer neutrino underwater telescope. The construction and commissioning of the detector infrastructure is currently underway. The Cherenkov Telescope Array (CTA) is the next generation ground-based observatory for gamma-ray astronomy at very-high energies. Both collaborations contributed to ESCAPE, the European Science Cluster of Astronomy and Particle Physics, which brings together many astrophysics and particle physics experiments to further open science in the community via the European Open Science Cloud (EOSC). The data, measured as individual events in both telescopes, motivates the use of common tools for analysis. In the multi-messenger era, investigation of a specific scientific question from different experiments in a synergic approach yields significant additional insights not achievable with information from one messenger alone. This approach was successfully employed in a combination of simulated data from the high-energy array of KM3NeT (ARCA) and CTA to distinguish between leptonic and hadronic emission scenarios of gamma-ray sources in the Milky Way using a common software framework. This contribution demonstrates the successful deployment of the analysis into the EOSC/ESCAPE thematic cluster infrastructure for future usage in the open science regime.
CRIS-Team Scopus Importer:2024-04-12